Voltage Cycling Induced Losses in Electrochemically Active Surface Area and in H2/Air-Performance of PEM Fuel Cells. Issue 6 (9th March 2016) - Zihrul, Patrick; Hartung, Ingmar; Kirsch, Sebastian; Huebner, Gerold; Hasché, Frédéric; Gasteiger, Hubert A.
Abstract : The influence of voltage cycling profiles on the degradation of MEAs (membrane electrode assemblies) for PEM (proton exchange membrane) fuel cells was investigated using MEAs with carbon supported catalysts. The loss of electrochemically active surface area (ECSA) of the cathode electrodes significantly increased with the upper potential limit. The ECSA loss was correlated with the performance decrease for hydrogen/air polarization curves, revealing purely kinetic losses at low and additional mass-transport related voltage losses at high platinum surface area normalized current densities (≡specific current densities). The absolute voltage losses only depended on the specific current density, independent of the extent of ECSA loss and the geometric current density.